Improving The Quality Of Fire Service In Bone District - Ramli, Andi; H, Herman; Halim, Didin; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2024)
This study aims to identify and describe the dimensions in the SERVQUAL model that are most effective in improving the quality of service of the Fire Department in Bone Regency. The type of research is descriptive qualitative. Data collection techniques through observation, interviews and documentation. Data analysis techniques include data condensation, data presentation, and drawing conclusions. The results showed that the five dimensions in the SERVQUAL model tangibles, reliability, responsiveness, assurance, and empathy play an important role in improving the service quality of the UPT Fire Department in Bone Regency. In the tangibles dimension, although equipment and vehicles are available, their modernity is still lacking, so they need to be improved to support service effectiveness. In the reliability dimension, the response speed is quite good, but the community still feels that the response time is not sufficient, indicating a difference in perception that needs to be harmonized. In the responsiveness dimension, officers are quite responsive to emergency reports, but consistency in handling various situations still needs to be improved. On the assurance dimension, training and certification of officers is good enough, but needs to be further improved so that officers are better prepared and the public has more confidence in their abilities. In the empathy dimension, the attitude of attention and concern of officers towards the community has not been evenly distributed, so that services have not fully provided the expected sense of comfort and support. Then the supporting factors are good, this can be seen from the competence and dedication of officers who are starting to improve even though routine training is needed, there is cooperation with the community that has the potential to be developed, as well as budget support and regional policies which, although limited, have supported operations. Inhibiting factors, there are still obstacles such as limited facilities and infrastructure. Keywords: Service Quality, SERVQUAL Model, Fire Department